Financial Sector Assessment : Serbia - World Bank (Washington, DC, 2013)
This Financial Sector Assessment presents the Bank's policy recommendations following an analysis of Albania's financial system, currently broadly stable, but with systemic risks which could come to the fore if the rapid pace of credit growth continues. Policies to support financial stability, and development should focus mostly on bank supervision, and the legal framework, while policies to remove impediments to the development of the nascent insurance sector are underway. Not surprisingly, the creation of a supporting legal framework is currently the main issue for capital markets. But monetary policy effectiveness should be strengthened by adjustments to the monetary operation framework, and the establishment of an interest rate bureau. Regarding corporate governance, much remains to be done. The authorities should eliminate discrepancies between the general-purpose financial reporting under the International Financial Reporting Standards (IFRS) and the regulatory reporting. Moreover, macroeconomic imbalances are rooted in structural problems in state- and socially-owned enterprises which account for 50 percent of GDP. Regarding prudential supervision issues, the NBS Bank Supervision Department (BSD) has made progress in enhancing effectiveness; however, the Basel Core Principles assessment of bank supervision was unfavorable.